To fly among the stars : the hidden story of the fight for women astronauts - Siegel, Rebecca (Scholastic Focus, 2020)
Presents an account of the thirteen women who trained alongside the Mercury Seven in the early 1960s for a chance to be selected as astronauts. Examines the sexism they endured, their test results, which proved they were as capable as the men, and their contributions toward opening up astronautics to women. Features photographs and a glossary.